Investigating the implementation of Panji culture-based cultural entrepreneurship - I Dewa Gde Satrya (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to explore the implementation of Panji culture-based cultural entrepreneurship.Method — This study used a qualitative method, gathering primary data through interviews with Panji mask dance artists and experts at Sanggar Tari Asmorobangun, Panji museum in Malang, and Gubug Wayang Museum in Mojokerto. Secondary data was obtained from relevant literature.Result — The implementation of Panji cultural entrepreneurship involves various aspects such as museums showcasing Panji masks and artifacts, the integration of Panji performances in dance studios and art galleries, and the promotion of Panji culture through handicrafts. These initiatives aim to preserve and promote Panji culture, educate younger generations, attract tourists, and contribute to the creative economy in Indonesia.Contribution — This study contributes by discussing the implementation of Panji culture-based cultural entrepreneurship, filling a research gap in the literature and providing insights into the strategies and initiatives employed in preserving and promoting Panji culture.